A Framework for intelligent condition-based maintenance of rotating equipment using mechanical condition monitoring - Mohammadreza Tahan, B. (EDP Sciences, 2014)
The ideal end result of maintenance strategy is to increase profitability, improve product quality and ensure safety conditions. In condition-based maintenance (CBM), asset health is monitored regularly to maximize reliability and availability by determining necessary maintenance at the right time. Review of recent studies shows most of developed approaches propose a standalone system for each stage of maintenance system. In order to standardize a generic architecture for machinery CBM, this paper attempts to introduce an intelligent framework consisting of several functional modules, starting from data acquisition and ending to advisory generation, with the emphasis on approaches of condition monitoring and maintenance decision-making. Â© 2014 Owned by the authors, published by EDP Sciences.